Desenvolvimento de um dispositivo lúdico para auxiliar crianças com transtorno de desenvolvimento cognitivo - Dantas, Vanessa Caroline Freire (2018)
The use of new technologies promotes, in addition to facilitating the daily tasks of people, social development. Games and robots, for example, have been used to help people with some disorder, whether related to psychological distress: anxiety, depression, schizophrenia; or related to cognition: mental deficiency, autism, among others. Thus, the present work has the objective of developing a playful device that may favor the development of abilities such as interaction, laterality and logical reasoning of children with some cognitive developmental disorder. It consists of three wooden touch pads that are connected to the computer, allowing the child to control a game on the computer. Its validation was carried out by means of specialists, following the methodology TAM (Technology Acceptance Model). The results showed that the device developed can be used as a means to aid in the daily activities of the specialists